A biomolecular archaeological approach to ‘Nordic grog’ - McGovern, Patrick E.; Hall, Gretchen R.; Mirzoian, Armen (Danish Journal of Archaeology, 2013)
The combined archaeological, biomolecular, and archaeobotanical evidence from four sites in Denmark (Nandrup, Kostræde, and Juellinge) and Sweden (Havor on the island of Gotland) provide key reference points for reconstructing ‘Nordic grog’ from ca. 1500 BC to the first century AD. In general, Nordic peoples preferred a hybrid beverage or ‘grog,’ in which many ingredients were fermented together, including locally available honey, local fruit (e.g., bog cranberry, and lingonberry) and cereals (wheat, rye, and/or barley), and sometimes grape wine imported from farther south in Europe. Local herbs/spices, such as bog myrtle, yarrow and juniper, and birch tree resin rounded out the concoction and provide the earliest chemical attestations for their use in Nordic fermented beverages. The aggregate ingredients probably served medicinal purposes, as well as contributing special flavors and aromas. They continued to be important ingredients for many kinds of beverages throughout medieval times and up to the present. The importation of grape wine from southern or central Europe as early as ca. 1100 BC, again chemically attested here for the first time, is of considerable cultural significance. It demonstrates the social and ceremonial prestige attached to wine, especially when it was served up as ‘Nordic grog’ in special wine-sets imported from the south. It also points to an active trading network across Europe as early as the Bronze Age in which amber might have been the principle good exchanged for wine. The presence of pine resin in the beverages likely derives from the imported wine, added as a preservative for its long journey northward.